High throughput production of single-wall carbon nanotube fibres independent of sulfur-source. Issue 39 (2nd October 2019) - Kaniyoor, Adarsh; Bulmer, John; Gspann, Thurid; Mizen, Jenifer; Ryley, James; Kiley, Patrick; Terrones, Jeronimo; Miranda-Reyes, Cesar; Divitini, Giorgio; Sparkes, Martin; O'Neill, Bill; Windle, Alan; et al.
Abstract : Rapidly jetting precursors in floating catalyst chemical vapor deposition produces monodisperse, metallic single-wall carbon nanotube fibres, irrespective of sulfur source. Abstract : Floating catalyst chemical vapor deposition (FC-CVD) methods offer a highly scalable strategy for single-step synthesis and assembly of carbon nanotubes (CNTs) into macroscopic textiles. However, the non-uniform axial temperature profile of a typical reactor, and differing precursor breakdown temperatures, result in a broad distribution of catalyst particle sizes. Spun CNT fibres therefore contain nanotubes with varying diameters and wall numbers. Herein, we describe a general FC-CVD approach to obtain relatively large yields of predominantly single-wall CNT fibres, irrespective of the growth promoter (usually a sulfur compound). By increasing carrier gas (hydrogen) flow rate beyond a threshold whilst maintaining a constant C : H2 mole ratio, CNTs with narrower diameters, a high degree of graphitization (G : D ratio ∼100) and a large throughput are produced, provided S : Fe ratio is sufficiently low. Analysis of the intense Raman radial breathing modes and asymmetric G bands, and a shift in the main nanotube population from thermogravimetric data, show that with increasing flow rate, the fibres are enriched with small diameter, metallic CNTs. Transmission electron microscopy corraborates our primary observation from Raman spectroscopy that with high total flow rates, the fibres produced consist of predominantly small diameter SWCNTs.